The incorporation of women into the teaching profession in the first faculties of the central univer- sity of madrid (1910-1939) - Izquierdo Expósito, Violeta; Lima Guerrero, David (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This paper focuses on the initial stage of the process of incorporating women into the practice of teaching in the first faculties which formed part of the Central University of Madrid, from the time when legislation made it possible, in 1910, until the end of the Civil War. The circumstances and factors that made women's access to teaching possible have been analysed, taking into account previous contributions through an in-depth bibliographical review, and an exhaustive list of women professors has been drawn up, classified by faculty, which recovers and extends the data obtained in other research through new explorations in the historical archives.